Can I Borrow Your Phone? Understanding Concerns When Sharing Mobile Phones - Karlson, Amy; Brush, A.J.; Schechter, Stuart (Proceedings of CHI 2009, 2009)
Mobile phones are becoming increasingly personalized in terms of the data they store and the types of services they provide. At the same time, field studies have reported that there are a variety of situations in which it is natural for people to share their phones with others. However, most mobile phones support a binary security model that offers all-or-nothing access to the phone. We interviewed 12 smartphone users to explore how security and data privacy concerns affected their willingness to share their mobile phones. The diversity of guest user categorizations and associated security constraints expressed by the participants suggests the need for a security model richer than today’s binary model.